A PORTFOLIO- BASED WRITING ASSESSMENT ON STUDENTS’ ABILITY IN WRITING A DESCRIPTIVE TEXT - Arrista Berliana J; Saunir Saun; Yuli Tiarina (Universitas Negeri Padang, 2013)
Abstract The purpose of this research was to test whether the effect of using the portfolio- based writing assessment as an alternative assessment had better achievement on students’ writing ability of descriptive text. The research used posttest only design, which means that students’ ability in writing descriptive text was measured after the students were given a treatment. The population and samples of this research were students of X grades in SMA Negeri 17 Tebo. The instrument of this research was writing test to write a descriptive text. The result of this research showed that there was significant effect to the experimental group after getting the treatment. So that, the portfolio- based writing assessment could give better effect to students’ writing ability in writing descriptive text. Kata Kunci : Portfolio- based writing assessment, Kemampuan Menulis, Descriptive text